2016
DOI: 10.1186/s12917-016-0758-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Aujeszky’s disease in wild boar in Serbia

Abstract: BackgroundAujeszky’s disease is a viral disease of suids caused by Suid Herpesvirus 1. The disease has worldwide distribution with significant economic impact. In Serbia, there is neither an Aujeszky’s disease eradication nor national vaccination programme of domestic pigs.Since clinical symptoms of Aujeszky’s disease are not specific, it is important to establish a link between clinical signs and presence of ADV active infection in wild boars. The aim of this study was to investigate the possibility of active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…It is well known that PRV strains can spill over from the wild boar population to the domestic pig population and vice versa. Such bidirectional transmissions have been experimentally demonstrated [31,32], and phylogenetic analyses have confirmed that strains related to wild boars can cluster with those related to domestic pigs [11,33,34]. This is indeed the case here, with two French strains isolated from hunting dogs belonging to I-A Group 1 clustering with strains isolated from domestic pigs in other countries.…”
Section: Discussionsupporting
confidence: 78%
“…It is well known that PRV strains can spill over from the wild boar population to the domestic pig population and vice versa. Such bidirectional transmissions have been experimentally demonstrated [31,32], and phylogenetic analyses have confirmed that strains related to wild boars can cluster with those related to domestic pigs [11,33,34]. This is indeed the case here, with two French strains isolated from hunting dogs belonging to I-A Group 1 clustering with strains isolated from domestic pigs in other countries.…”
Section: Discussionsupporting
confidence: 78%
“…The presence of free-ranging pigs in some areas in the region may contribute to the possible spread of ASF in the ROC. This has been demonstrated in the past for other diseases, such as Aujeszky's disease or brucellosis in the ROC (Duvnjak et al, 2015;Milicevic et al, 2016;Zutic et al, 2017). Free-ranging pig farming is a traditional husbandry practice in most countries in the ROC.…”
Section: 1mentioning
confidence: 95%
“…). In Serbia, WB and DP also share similar Suid Herpesvirus 1 strains (Aujeszky's disease; Milicevic et al., ). Further, farmed wild boar are present in Bosnia and Herzegovina for the purpose of training hunting dogs (Zahirovic et al., ) and Marinou et al.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease is controlled by containment of infected herds and by the use of vaccines or removal of latently infected animals (2). However, SHV-1 is being continuously reported in the wild boar population across Europe and in hunting dogs (3). …”
Section: Genome Announcementmentioning
confidence: 99%